PENGARUH KOMUNIKASI INTERNAL DAN KERJASAMA TIM TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KABUPATEN TORAJA UTARA - Kinni, Iga Deswyta; Tangkeallo, Dian Intan; Pagiu, Chrismesi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The aim of this research is to find out whether there is an influence of Internal Communication and Teamwork on Employee Work Productivity at the Toraja Regency Personnel and Human Resources Development Agency. The data collection procedures for this research are: observation, questionnaires, and documentation. The method used in this research is the Quantitative Method using the Multiple Linear Regression method and processed using SPSS 26 The technique that researchers use in sampling is the census method (total sampling), namely a sampling method using all members of the population a total of 31. The results of calculations using the t test on the Internal Communication variable t count > t table with a value of (3.090) > (2.04841) and on the Team Collaboration variable t count > t table with a value of (10.280) > (2.04841). The conclusion of this research is that Internal Communication and Teamwork have a positive and significant effect on employee work productivity at the Toraja Regency Personnel and Human Resources Development Agency.